Controlled-release microspheres cyanide leaching aid and preparation method thereof and cyanide leaching process

CN122918345APending Publication Date: 2026-10-16CHANGCHUN GOLD RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611385005.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-16

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a controlled-release microsphere cyaniding leaching aid and a preparation method and a cyanide leaching gold process, and belongs to the field of gold hydrometallurgy. The SR-K2S2O8 drug-loaded micro powder is obtained by at least one potassium persulfate loading treatment on mesoporous silica powder, at least one chitosan immersion treatment is performed, cross-linking treatment is performed, and a wet-state filter cake after chitosan cross-linking is obtained after filtration, which is granulated and dried to obtain mesoporous silica loaded potassium persulfate-chitosan controlled-release microsphere cyaniding leaching aid. The application loads potassium persulfate in the mesoporous silica powder channel, and coats a cross-linked chitosan shell layer to regulate the release rate, realizes dynamic matching of oxidant supply and mineral demand, and simultaneously utilizes the characteristics of in-situ activation of potassium persulfate to generate sulfate radicals to realize directional oxidative damage of the sulfide passivation film, thereby significantly reducing cyanide consumption while improving gold leaching rate. 2+ The application provides a controlled-release microsphere cyaniding leaching aid and a preparation method and a cyanide leaching gold process, and belongs to the field of gold hydrometallurgy. The SR-K2S2O8 drug-loaded micro powder is obtained by at least one potassium persulfate loading treat
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of gold hydrometallurgy, specifically to a controlled-release microsphere cyanide leaching aid, its preparation method, and cyanide leaching gold process. Background Technology

[0002] Traditional cyanide leaching gold processes face the following key bottlenecks in actual production: insufficient dissolved oxygen limits the leaching rate, passivation of sulfide mineral surfaces hinders gold exposure, existing leaching aids still have room for improvement in terms of release controllability, and secondary resource cyanide leaching faces special challenges.

[0003] Therefore, there is an urgent need to develop a novel cyanide leaching aid that integrates the functions of controlled oxidant release, in-situ activation and directional oxidation, and reduced cyanide consumption. This is not only applicable to refractory gold ores but also effectively solves the technical challenges in cyanide leaching of secondary resources, and is a pressing need in the current gold hydrometallurgical field. Summary of the Invention

[0004] This application provides a controlled-release microsphere cyanide leaching aid, its preparation method, and cyanide leaching gold process, aiming to solve the technical problems of uncontrollable oxidant release, high ineffective consumption of cyanide, and low removal efficiency of sulfide passivation film in existing cyanide leaching gold aids.

[0005] In a first aspect, embodiments of this application provide a method for preparing a controlled-release microsphere cyanide leaching aid, characterized by comprising the following steps: S1. Provide mesoporous silica powder; S2. The mesoporous silica powder is subjected to at least one potassium persulfate loading treatment to obtain SR-K2S2O8 drug-loaded micro powder; wherein, the potassium persulfate loading treatment includes: immersing the mesoporous silica powder in a saturated aqueous solution of potassium persulfate, removing it after thorough immersion and drying it. S3. The SR-K2S2O8 drug-loaded micro powder is subjected to at least one chitosan impregnation treatment, followed by cross-linking treatment, and filtered to obtain a wet filter cake after chitosan cross-linking. S4. Granulate and dry the wet filter cake to obtain a mesoporous silica-supported potassium persulfate-chitosan controlled-release microsphere cyanide impregnation aid.

[0006] Furthermore, in step S1, the mesoporous silica powder is synthesized using a template method; and / or, Mesoporous silica has a specific surface area of ​​500–1000 m² / g and a pore size of 2–10 nm.

[0007] Furthermore, in step S2, the pressure of the potassium persulfate loading treatment is -0.1 to -0.08 MPa, the liquid-solid ratio of the saturated potassium persulfate aqueous solution to the mesoporous silica powder is 5:1 to 10:1, and the treatment time is 30 to 60 min; drying is carried out under vacuum conditions at a temperature of 40 to 60 °C for 12 to 24 h.

[0008] Furthermore, the potassium persulfate loading is 8% to 15% of the mass of mesoporous silica.

[0009] Furthermore, in step S3, the chitosan impregnation treatment time is 10-30 s, and the steps include: immersing the SR-K2S2O8 drug-loaded micro powder in the chitosan solution, taking it out and drying it for 10-20 min; The chitosan solution is prepared by dissolving chitosan in a 0.5–1.5 vol% aqueous acetic acid solution, with a mass concentration of 1%–4%, a degree of deacetylation of chitosan ≥90%, and a molecular weight of 50,000–150,000 Da.

[0010] Furthermore, in step S3, the cross-linking treatment includes: adding the micro powder obtained after chitosan impregnation treatment to a glutaraldehyde aqueous solution with a mass concentration of 5% to 10% to carry out a cross-linking reaction; The mass ratio of glutaraldehyde to chitosan in the glutaraldehyde aqueous solution is 1–3:10; the degree of cross-linking reaction is 10%–30%, the reaction temperature is 25–35℃, and the reaction time is 1–3 h.

[0011] Secondly, embodiments of this application provide a controlled-release microsphere cyanide leaching aid, which is prepared using any of the above-mentioned preparation methods.

[0012] The impregnation aid includes core-shell structured microspheres, which consist of a mesoporous silica carrier core and a chitosan controlled-release shell. The mesoporous silica carrier core is loaded with potassium persulfate in its mesoporous channels, and the chitosan controlled-release shell coats the surface of the mesoporous silica carrier core.

[0013] Furthermore, the average particle size of the mesoporous silica carrier core is 50–200 nm; the thickness of the chitosan controlled-release shell is 50–300 nm; and the total particle size of the impregnating agent microspheres is 300–500 μm.

[0014] Thirdly, this application provides a cyanide leaching gold process, which uses a controlled-release microsphere cyanide leaching aid to perform cyanide leaching gold, including the following steps: pretreating the gold-containing material to obtain gold-containing powder; The gold-bearing powder was subjected to a slurry preparation process to obtain the first slurry; An alkaline pH adjuster is added to the first slurry to obtain the second slurry; Sodium cyanide was added to the second slurry to obtain the third slurry; Controlled-release microsphere cyanide leaching aid was added to the third ore slurry, and the mixture was stirred and leached to obtain a gold-containing cyanide precious solution.

[0015] Further, the pretreatment includes grinding or crushing; and / or, the gold powder concentration of the first slurry is 20% to 45%; and / or, the pH of the second slurry is 10 to 11.5; and / or, the free cyanide concentration of the third slurry is 0.02% to 0.15%; and / or, the amount of controlled-release microsphere cyanide leaching aid is 0.2 to 10.0 kg / t.

[0016] The beneficial technical effects of this application are as follows: 1. This application provides a controlled-release microsphere cyanide leaching aid, its preparation method, and cyanide leaching gold process. For the first time, a mesoporous nanocarrier-controlled-release shell structure is introduced into the field of cyanide leaching gold aids, realizing dynamic matching between the oxidant release rate and the leaching oxygen consumption curve, fundamentally solving the problem of release imbalance of existing aids, which is "excessive in the early stage and insufficient in the later stage".

[0017] 2. This application provides a controlled-release microsphere cyanide leaching aid, its preparation method, and a cyanide leaching gold process, utilizing S2O8. 2- Fe on the surface of sulfide minerals 2+ In-situ activation produces SO4• - SO4• - It reacts with the sulfide surface at the point of generation, achieving directional destruction of the passivation film, rather than the indiscriminate oxidation of cyanide and sulfide in traditional leaching aids.

[0018] 3. The controlled-release microsphere cyanide leaching aid, its preparation method, and the cyanide leaching gold process provided in this application reduce the amount of sodium cyanide used by 15% to 30% compared with the traditional process through a slow-release rate control mechanism, while reducing the residual amount of cyanide and cyanate in the tailings, and significantly reducing cyanide consumption.

[0019] 4. The controlled-release microsphere cyanide leaching aid, its preparation method, and cyanide gold leaching process provided in this application can increase the gold leaching rate by 3 to 8 percentage points and shorten the leaching time by 20% to 40% in the cyanide leaching of refractory gold ores containing sulfides, compared with the traditional cyanide leaching process without the aid. Moreover, the raw materials such as mesoporous silica, chitosan, and potassium persulfate are widely available, the microsphere preparation process is simple, and it is suitable for large-scale production.

[0020] 5. The controlled-release microsphere cyanide leaching aid, its preparation method, and cyanide leaching gold process provided in this application are applicable to the cyanide leaching enhancement of various gold ores, especially for refractory gold ores containing sulfide gangue minerals (pyrite, arsenopyrite, etc.), and have a wide range of applications.

[0021] 6. The controlled-release microsphere cyanide leaching aid, its preparation method, and the cyanide gold leaching process provided in this application all exhibit excellent leaching enhancement effects on residual gold highly coated with iron oxides in cyanide tailings, gold blocked in the micropores of waste precious metal catalysts, and leaching inhibition caused by the gold-stealing effect on the surface of fresh sulfides in gravity concentrates. It also has strong applicability to secondary resources.

[0022] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Detailed Implementation

[0023] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are intended to cover non-exclusive inclusion.

[0025] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0026] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0027] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0028] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0029] Unless otherwise specified, the terms "comprising" and "including" as used in this application are open-ended. For example, "comprising" and "including" may mean that other components not listed may also be included or contained.

[0030] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0031] To address the technical problems of uncontrollable oxidant release, high ineffective cyanide consumption, and low sulfide passivation film removal efficiency in existing cyanide leaching aids, this application provides a controlled-release microsphere cyanide leaching aid, its preparation method, and cyanide leaching process. By subjecting mesoporous silica powder to at least one potassium persulfate loading treatment to obtain SR-K2S2O8 loaded micropowder, followed by at least one chitosan impregnation treatment, and then a cross-linking reaction, a wet filter cake of chitosan cross-linked material is obtained after filtration. This cake is then granulated and dried to obtain the mesoporous silica-loaded potassium persulfate-chitosan controlled-release microsphere cyanide leaching aid. Through these steps, a novel cyanide leaching aid with three integrated functions—controlled oxidant release, in-situ activation and directional oxidation, and reduced cyanide consumption—is developed. This aid is not only suitable for refractory gold ores but also effectively solves the technical challenges in cyanide leaching of secondary resources, meeting the urgent needs of the current gold hydrometallurgical field.

[0032] In a first aspect, embodiments of this application provide a method for preparing a controlled-release microsphere cyanide leaching aid, comprising the following steps: S1. Provide mesoporous silica powder; S2. The mesoporous silica powder is subjected to at least one potassium persulfate loading treatment to obtain SR-K2S2O8 drug-loaded micro powder; wherein, the potassium persulfate loading treatment includes: immersing the mesoporous silica powder in a saturated aqueous solution of potassium persulfate, removing it after thorough immersion and drying it. S3. The SR-K2S2O8 drug-loaded micro powder is subjected to at least one chitosan impregnation treatment, followed by cross-linking treatment, and filtered to obtain a wet filter cake after chitosan cross-linking. S4. Granulate and dry the wet filter cake to obtain a mesoporous silica-supported potassium persulfate-chitosan controlled-release microsphere cyanide impregnation aid.

[0033] In the technical solution of this application embodiment, the above steps S1 to S4 constitute a complete preparation chain of "carrier provision → oxidant loading → shell coating and crosslinking → granulation and molding", the core of which lies in constructing controlled-release microspheres with a core-shell structure. First, in step S1, mesoporous silica powder is provided, which has ordered mesoporous channels and high specific surface area, and can be used as a loading carrier for potassium persulfate. Its mesoporous channels provide confined space for the subsequent physical loading of oxidant. In step S2, a saturated potassium persulfate solution is introduced into the mesoporous channels through impregnation treatment. After drying, potassium persulfate crystallizes and deposits in the channels. Repeated loading can increase the loading amount, resulting in SR-K2S2O8 drug-loaded micropowder. In step S3, the drug-loaded micropowder is impregnated in a chitosan solution. Chitosan is deposited on the surface of the micropowder to form a coating layer. Subsequently, crosslinking treatment can enhance the structural stability and water resistance of the shell layer, reduce its swelling degree in water, and thus form a dense controlled-release barrier on the surface of the drug-loaded micropowder. It is understandable that the density of the cross-linked chitosan shell can affect the release rate of potassium persulfate to a certain extent, which is the structural basis for achieving the controlled-release function in this application. Further, in step S4, the cross-linked wet filter cake is extruded and granulated to form particles. These four progressive steps ultimately form core-shell microspheres with potassium persulfate supported on mesoporous silica as the core and cross-linked chitosan as the controlled-release shell, achieving controlled-release of potassium persulfate through the physical barrier effect of the shell.

[0034] It can be noted that, in some embodiments, granulation in step S4 involves extruding the wet filter cake through a 20-mesh sieve to obtain cylindrical wet granules. During this process, chitosan acts as a granule binder while coating the SR-K2S2O8 drug-loaded micropowder, agglomerating the nano-sized SR-K2S2O8 drug-loaded micropowder into granules. After granulation, drying yields a controlled-release microsphere cyanide co-extraction agent; preferably, the drying temperature is 40–60°C, and the drying time is 4–8 hours.

[0035] Furthermore, in step S1, the silica powder is synthesized using a template method.

[0036] In the technical solutions of this application, the template method is one of the most commonly used methods for synthesizing ordered mesoporous materials. Its core principle is to use micelles or liquid crystal phases formed by the self-assembly of surfactant molecules in solution as templates. Inorganic precursors hydrolyze and condense around the template to form an inorganic framework. Subsequently, the template is removed by calcination or solvent extraction, leaving ordered mesoporous channels in the inorganic framework corresponding to the template morphology. The template method in this application includes the following steps: dissolving cetyltrimethylammonium bromide (CTAB) in deionized water, heating, adjusting the pH, adding tetraethyl orthosilicate (TEOS) under stirring, reacting at a constant temperature, centrifuging and filtering, washing, and calcining. Specifically, the heating temperature is 60–80°C, the pH is adjusted to 10–12, the molar ratio of cetyltrimethylammonium bromide to tetraethyl orthosilicate is 1:4–6, the constant temperature stirring reaction time is 2–4 h, the calcination temperature is 500–600°C, and the calcination time is 4–6 h. MCM-41 type mesoporous silica is preferably synthesized under alkaline conditions using CTAB as a template agent and TEOS as a silicon source. CTAB molecules can form hexagonal rod-shaped micelles in aqueous solution. After hydrolysis and condensation of TEOS, a silica framework is deposited on the surface of the micelles. After calcination to remove CTAB, the MCM-41 structure with hexagonal ordered mesoporous channels is obtained.

[0037] Furthermore, in step S1, the mesoporous silica has a specific surface area of ​​500–1000 m² / g and a pore size of 2–10 nm.

[0038] In the technical solutions of this application embodiment, the specific surface area and pore size of mesoporous silica are key structural parameters affecting the loading and release behavior of potassium persulfate. If the specific surface area is too small, the available adsorption sites are limited, making it difficult to achieve a potassium persulfate loading of over 8%. If the specific surface area is too high, although the loading can be further increased, the preparation difficulty and cost increase, and an excessively high specific surface area may lead to excessively thin pore walls and decreased structural stability. A pore size in the range of 2-10 nm can meet the space requirements for potassium persulfate molecules (kinetic diameter approximately 0.7-0.8 nm) to enter the pores and crystallize and deposit therein. If the pore size is too small, potassium persulfate molecules cannot enter effectively; if the pore size is too large, the released rate of the loaded potassium persulfate during subsequent processing is too fast, which is not conducive to the construction of the subsequent controlled-release shell layer.

[0039] Furthermore, in step S2, the pressure of the potassium persulfate loading treatment is -0.1 to -0.08 MPa, the liquid-solid ratio of the saturated potassium persulfate aqueous solution to the mesoporous silica powder is 5:1 to 10:1, and the soaking time is 30 to 60 min; drying is carried out under vacuum conditions at a temperature of 40 to 60 °C for 12 to 24 h.

[0040] In the technical solution of this application embodiment, the loading process uses vacuum conditions to remove air from the mesoporous channels, allowing the potassium persulfate solution to fully penetrate into the mesoporous channels. When the pressure is below -0.08 MPa (i.e., the vacuum degree is above 0.08 MPa), the air in the channels is effectively expelled; if the vacuum degree is insufficient, residual air may hinder the penetration of the solution, affecting the loading efficiency. A suitable liquid-to-solid ratio ensures that the mesoporous silica powder is fully wetted, while avoiding reagent waste caused by an excessively high liquid-to-solid ratio. A suitable processing time allows the potassium persulfate solution to reach equilibrium adsorption within the channels. Drying is carried out under vacuum conditions at a suitable temperature because potassium persulfate is heat-sensitive, and excessively high temperatures may cause it to decompose; vacuum conditions accelerate solvent evaporation, shorten drying time, and avoid the influence of moisture in the air on the loading effect. A suitable drying time ensures that the solvent in the channels is fully removed, allowing the potassium persulfate to completely crystallize and deposit within the channels.

[0041] Furthermore, the potassium persulfate loading is 8% to 15% of the mass of mesoporous silica.

[0042] In the technical solution of this application embodiment, the loading amount of potassium persulfate determines the oxidant capacity and leaching aid ability of the microspheres. When the loading amount is too low, the amount of oxidant that can be released per unit mass of microspheres is insufficient, which may affect the oxidation driving force in the later stage of leaching. When the loading amount is too high, the amount of potassium persulfate deposited in the mesoporous channels may exceed the carrying capacity of the channels, resulting in some potassium persulfate existing in crystalline form on the outer surface of the mesoporous silica particles. This part of potassium persulfate may not be effectively covered by the chitosan shell during coating, affecting the controlled release effect. By controlling the loading amount within a reasonable range, it is possible to ensure that the potassium persulfate is mainly loaded inside the mesoporous channels while ensuring sufficient oxidant capacity, thereby being effectively coated by the chitosan shell and achieving controlled release.

[0043] Furthermore, in step S3, the chitosan impregnation process includes: immersing the SR-K2S2O8 drug-loaded micropowder in a chitosan solution, impregnating for 10–30 seconds, and then removing and air-drying for 10–20 minutes. The method for preparing chitosan solution includes: dissolving chitosan in a 0.5-1.5 vol% aqueous acetic acid solution; the chitosan solution has a mass concentration of 1%-4%, a degree of deacetylation of chitosan ≥90%, and a molecular weight of 50,000-150,000 Da.

[0044] In the technical solution of this application embodiment, the impregnation process achieves uniform deposition of chitosan on the surface of the drug-loaded micropowder through rapid impregnation. A reasonable impregnation time allows the drug-loaded micropowder surface to fully contact the chitosan solution, but excessive time may cause a small amount of potassium persulfate to dissolve in the aqueous solution. Drying allows the solvent to evaporate and chitosan to deposit on the micropowder surface to form a thin film. If the concentration and mass concentration of the chitosan solution are too low, the amount of chitosan deposited in a single impregnation is insufficient, requiring multiple impregnations to achieve the target shell thickness; if the concentration is too high, the solution viscosity is too high, which is not conducive to forming a uniform coating layer on the micropowder surface. Acetic acid, as a solvent, can dissolve chitosan to form a homogeneous solution. A suitable acetic acid concentration can meet the dissolution requirements of chitosan while avoiding the potential impact of excessive acidity on the stability of potassium persulfate. Chitosan has a deacetylation degree of ≥90% to ensure that it has enough free amino groups to participate in the cross-linking reaction; when the molecular weight is 50,000~150,000 Da, its solution viscosity is moderate, which is conducive to film formation and coating. If the molecular weight is too low, the film formation is poor, and if the molecular weight is too high, the solution viscosity is too high, which is not conducive to the coating operation.

[0045] Furthermore, in step S3, the cross-linking treatment includes: adding the micro powder obtained after chitosan impregnation treatment to a glutaraldehyde aqueous solution with a mass concentration of 5% to 10% to carry out a cross-linking reaction; The mass ratio of glutaraldehyde to chitosan in the glutaraldehyde aqueous solution is 1–3:10; the degree of cross-linking reaction is 10%–30%, the reaction temperature is 25–35℃, and the reaction time is 1–3 h.

[0046] In the technical solution of this application embodiment, the purpose of crosslinking treatment is to form chemical bonds between chitosan molecular chains, thereby enhancing the structural stability and barrier function of the shell layer. A suitable glutaraldehyde concentration provides sufficient aldehyde groups to react with the amino groups on chitosan via a Schiff base reaction; the mass ratio of glutaraldehyde to chitosan determines the crosslinking density. If the ratio is too low, crosslinking is insufficient, resulting in inadequate shell stability; if the ratio is too high, crosslinking is excessive, leading to an overly dense shell layer that may excessively hinder the release of potassium persulfate. Controlling the degree of crosslinking allows for a balance between shell stability and release rate. A reaction temperature of room temperature to slightly above room temperature is beneficial for the crosslinking reaction; a suitable time ensures the crosslinking reaction reaches its full extent. It is understood that the degree of crosslinking can be controlled by adjusting factors such as the amount of glutaraldehyde, reaction temperature, and reaction time. Those skilled in the art can determine suitable process conditions according to actual needs.

[0047] Secondly, embodiments of this application provide a controlled-release microsphere cyanide leaching aid, which is prepared using any of the above-mentioned preparation methods.

[0048] The impregnation aid includes core-shell structured microspheres, which consist of a mesoporous silica carrier core and a chitosan controlled-release shell. The mesoporous silica carrier core is loaded with potassium persulfate in its mesoporous channels, and the chitosan controlled-release shell coats the surface of the mesoporous silica carrier core.

[0049] In the technical solution of this application embodiment, the aforementioned core-shell structured microspheres achieve controlled-release of potassium persulfate through the physical barrier effect of the chitosan shell. Under cyanide leaching conditions, the swelling degree and porosity of the chitosan shell are affected by the cross-linking network and the solution environment. Potassium persulfate must first dissolve in the pores to form a solution, and then diffuse through the chitosan shell into the slurry. In this process, the chitosan shell acts as a rate-limiting barrier, effectively slowing down the release rate of potassium persulfate and maintaining it at a relatively stable level. The appropriate total particle size of the microspheres is suitable for the cyanide leaching slurry system, ensuring that the microspheres have good suspension and dispersion in the slurry, while not easily being lost with the fine particles of the tailings.

[0050] Furthermore, the average particle size of the mesoporous silica carrier core is 50–200 nm; the thickness of the chitosan controlled-release shell is 50–300 nm; and the total particle size of the impregnating agent microspheres is 300–500 μm.

[0051] In the technical solution of this application embodiment, the combination of the above-mentioned particle size ranges forms the structural basis for achieving effective controlled release. A suitable mesoporous silica carrier particle size ensures sufficient specific surface area and pore volume for potassium persulfate loading, while the nanoscale particle size facilitates the formation of a uniform core-shell structure during subsequent chitosan coating. A suitable chitosan shell thickness provides sufficient diffusion path length for the sustained release of potassium persulfate; if the shell is too thin, the barrier effect is insufficient, and the release rate remains too fast; if the shell is too thick, the mass transfer resistance is too high, potentially leading to a slow release rate and delayed impregnation effect. A suitable total particle size is achieved through granulation, balancing dispersibility and ease of operation for industrial applications.

[0052] Thirdly, this application provides a cyanide leaching gold process, which uses a controlled-release microsphere cyanide leaching aid to perform cyanide leaching gold, including the following steps: pretreating the gold-containing material to obtain gold-containing powder; The gold-bearing powder was subjected to a slurry preparation process to obtain the first slurry; An alkaline pH adjuster is added to the first slurry to obtain the second slurry; Sodium cyanide was added to the second slurry to obtain the third slurry; Controlled-release microsphere cyanide leaching aid was added to the third ore slurry, and the mixture was stirred and leached to obtain a gold-containing cyanide precious solution.

[0053] In the technical solution of this application embodiment, the above-mentioned cyanide leaching process is a complete process of leaching gold-containing materials by pretreatment, slurry preparation, alkali preparation, addition of cyanide, addition of leaching aid, and stirring. Its core lies in the synergistic cooperation between the controlled-release microsphere cyanide leaching aid and the cyanide leaching process. It is understood that in the cyanide leaching process, the dissolution of gold requires the joint participation of cyanide and oxidant—gold undergoes anodic dissolution in the alkaline cyanide solution to form Au(CN)₂. - Complexes are formed, and the cathode reaction requires oxygen or an oxidant to accept electrons to continue. When sulfide minerals are present in the slurry, the iron oxide / hydroxide passivation layer formed on their surface by oxidation hinders the contact between cyanide and gold. Simultaneously, the sulfide minerals themselves undergo side reactions with cyanide and dissolved oxygen, leading to increased cyanide and oxygen consumption. This application introduces a controlled-release microsphere cyanide leaching aid into a conventional cyanide leaching system. After the microspheres are added, the chitosan controlled-release shell can slow down the release rate of potassium persulfate inside, allowing S2O8 to... 2- By continuously releasing the oxidant into the slurry at a low concentration, the imbalance problem of excessive initial release and insufficient later release of immediate-release oxidants is avoided. (S2O8) 2- When Fe²⁺ diffuses to the surface of sulfide minerals, it is released by the minerals themselves. + In-situ activation produces SO4• - The active species, at the site of generation, directionally oxidizes the passivation layer on the sulfide surface, exposing the encapsulated gold to the cyanide solution. In this process, due to S₂O₈²⁻… - The release of [something] is regulated by the chitosan shell, and its free concentration in the slurry remains at a low level, thereby reducing S2O8² [something]. - Non-selective side reactions with cyanides and sulfides; simultaneously, SO4• - The generation and consumption of oxidants are concentrated on the surface of minerals, achieving "targeted" utilization of the oxidant. Through this mechanism, the cyanide leaching process can achieve a higher gold leaching rate with a lower sodium cyanide dosage, realizing a synergistic effect between leaching aid and cyanide reduction.

[0054] Further, the pretreatment includes grinding or crushing; and / or, the gold powder concentration of the first slurry is 20% to 45%; and / or, the pH of the second slurry is 10 to 11.5; and / or, the free cyanide concentration of the third slurry is 0.02% to 0.15%; and / or, the amount of controlled-release microsphere cyanide leaching aid is 0.2 to 10.0 kg / t.

[0055] In the technical solution of this application embodiment, the pretreatment makes the gold-containing material reach a suitable particle size, so that the gold minerals are fully dissociated and easy to contact with the solution; if the concentration of gold powder in the first slurry is too low, it will reduce the equipment utilization efficiency and increase the processing cost, while if it is too high, it will affect the mass transfer and stirring effect; the pH range of the second slurry can inhibit the hydrolysis of cyanide and maintain the optimal reaction conditions for cyanide leaching; if the concentration of free cyanide in the third slurry is too low, the gold dissolution rate will be insufficient, while if it is too high, it will increase cyanide consumption and environmental pressure; the amount of controlled-release microsphere cyanide leaching aid can be flexibly adjusted according to the sulfide content and passivation degree in the ore. When the sulfide content is high and the passivation is severe, the amount can be appropriately increased, and vice versa.

[0056] It should be noted that in this application, the amount of controlled-release microsphere cyanide leaching aid is 0.2 to 10.0 kg / t, which means that the amount of controlled-release microsphere cyanide leaching aid per ton of gold-containing material is 0.2 to 10.0 kg.

[0057] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0058] I. Preparation Method Example 1 This embodiment provides a method for preparing a controlled-release microsphere cyanide leaching aid, specifically including the following steps: S1. Dissolve 2.0 g CTAB in 400 mL deionized water, heat to 70℃ until completely dissolved, and adjust the pH to 11 with 2 mol / L NaOH solution. Add 10 mL TEOS dropwise under vigorous stirring. After stirring at a constant temperature for 3 h, cool to room temperature, centrifuge, and wash three times each with deionized water and anhydrous ethanol. Calcinate the white precipitate in a muffle furnace at 550℃ for 6 h at a heating rate of 2℃ / min to obtain mesoporous silica powder (MCM-41). BET nitrogen adsorption method analysis shows that the specific surface area of ​​the mesoporous silica powder is 820 m² / g, the pore size is 3.2 nm, and the pore volume is 0.95 cm³ / g.

[0059] S2. Immerse 5.0 g of the above MCM-41 powder in 50 mL of a saturated aqueous solution of K2S2O8 (solubility approximately 50 g / L at 25℃), place in a vacuum drying oven, and vacuum impregnate for 45 min at -0.09 MPa and 25℃. After removal, vacuum dry at 50℃ and -0.09 MPa for 18 h to complete the first round of potassium persulfate loading treatment. Repeat the above potassium persulfate loading treatment once to further deposit K2S2O8 in the pores, obtaining SR-K2S2O8 drug-loaded micropowder. In this SR-K2S2O8 drug-loaded micropowder, the loading amount of K2S2O8 is 9.5 wt% of the mass of mesoporous silica.

[0060] S3. Dissolve 2.0 g of chitosan in 200 mL of 1 vol% acetic acid solution and stir until completely dissolved to obtain a chitosan solution with a mass concentration of approximately 1%. Place 5.0 g of SR-K2S2O8 drug-loaded microparticles into a porous mesh basket and quickly immerse it in the chitosan solution for 20 seconds, then immediately remove it. Air dry for 15 minutes to allow chitosan to deposit on the surface of the microparticles. Repeat the immersion-drying process twice. Transfer the microparticles to 200 mL of deionized water containing 1.0 mL of 25 vol% glutaraldehyde aqueous solution and stir the mixture at 30°C for 2 hours to allow for crosslinking. Filter and quickly rinse twice with deionized water to obtain a wet filter cake with crosslinked chitosan, exhibiting a crosslinking degree of 21%.

[0061] S4. The wet filter cake is extruded and granulated through a 20-mesh sieve to obtain cylindrical wet particles. The wet particles are dried at 50℃ for 6 h. After the particles shrink, they are sieved and classified. Particles with a particle size range of 300-500 μm are collected to obtain a mesoporous silica-supported potassium persulfate-chitosan controlled-release microsphere cyanide impregnation aid.

[0062] Comparative Example 1 This comparative example provides a method for preparing a microsphere cyanide leaching aid. Compared with Example 1, the only difference is that steps S3-S4 are omitted, and the SR-K2S2O8 drug-loaded micro powder obtained in step S2 is directly used as the final cyanide leaching aid. The remaining steps are the same as in Example 1, and will not be repeated here.

[0063] Example 2 This embodiment provides a cyanide leaching process for gold, using the controlled-release microsphere cyanide leaching aid prepared in Example 1 to cyanide leach gold into an arsenic-bearing pyrite-type gold ore. This arsenic-bearing pyrite-type gold ore has an Au grade of 1.31 g / t, and its main gold-bearing minerals are native gold and argentite, with gangue minerals primarily consisting of pyrite and quartz. The cyanide leaching process includes the following steps: The ore was ground to a fineness of -0.074 mm (85%), and water was added to adjust the slurry concentration to 33%. Then, NaOH was added to adjust the pH of the slurry to 10.5, and then NaCN was added for cyanidation treatment. 1.6 kg of NaCN was added per ton of gold-containing material, i.e., the NaCN dosage was 1.6 kg / t (unless otherwise specified, the dosages involved in the examples and comparative examples below are calculated based on per ton of gold-containing material), and the free cyanide concentration of the slurry was controlled to be 0.05%. Then, the controlled-release microsphere cyanidation aid prepared in Example 1 (dosage was 1.0 kg / t) was added, and the mixture was stirred and leached at 25°C for 24 hours.

[0064] Comparative Example 2 This comparative example provides a cyanide leaching process for gold, which differs from Example 2 in that no leaching aid is added during the process; the dissolved oxygen in the slurry is used solely as the oxidant, and the amount of NaCN used is 2.0 kg / t. The remaining steps are the same as in Example 2 and will not be repeated here.

[0065] Comparative Example 3 This comparative example provides a cyanide leaching process for gold. Compared with Example 2, the difference is that the controlled-release microspheres prepared in Example 1 are not used for cyanide leaching. Instead, SR-K2S2O8 drug-loaded micropowder prepared in Comparative Example 1 is used for cyanide leaching. The dosage is 1.0 kg / t (added at once). The remaining steps are the same as in Example 2 and will not be repeated here.

[0066] Comparative Example 4 This comparative example provides a cyanide leaching process for gold, which differs from Example 2 only in that the controlled-release microsphere cyanide leaching aid prepared in Example 1 is not added; instead, CaO2 is added at the same amount of 1.0 kg / t. All other steps are the same as in Example 2 and will not be repeated here.

[0067] Example 3 This embodiment provides a cyanide leaching process for gold, using the controlled-release microsphere cyanide leaching aid prepared in Example 1 to leach gold from cyanide tailings stored in a gold mine stockpile. The cyanide tailings have an Au grade of 0.82 g / t. The residual gold in the tailings (approximately 65%) is encapsulated in the form of fine particles (<1 μm) by iron oxide / hydroxide, while the remaining 35% consists of incompletely dissociated fine gold particles. This cyanide leaching process includes the following steps: The cyanide tailings were crushed to a particle size of -0.074 mm (92%), and water was added to adjust the slurry concentration to 35%. Then, NaOH was added to adjust the pH of the slurry to 10.5, and NaCN was added for cyanidation treatment (NaCN dosage was 2.5 kg / t), controlling the free cyanide concentration of the slurry to 0.08%. Then, the controlled-release microsphere cyanidation aid prepared in Example 1 (dosage was 3.0 kg / t) was added, and the mixture was stirred and leached at 30°C for 48 hours.

[0068] Comparative Example 5 This comparative example provides a cyanide leaching process for gold, which differs from Example 3 in that no leaching aid is added during the process; the dissolved oxygen in the slurry is used solely as the oxidant, and the amount of NaCN used is 3.0 kg / t. The remaining steps are the same as in Example 3 and will not be repeated here.

[0069] Comparative Example 6 This comparative example provides a cyanide leaching process for gold, which differs from Example 3 in that the controlled-release microsphere cyanide leaching aid prepared in Example 1 is not added; instead, oxalic acid is added at a dosage of 2.0 kg / t. The remaining steps are the same as in Example 3 and will not be repeated here.

[0070] Example 4 This embodiment provides a cyanide leaching gold process, using the controlled-release microsphere cyanide leaching aid prepared in Example 1 to leach gold from a spent precious metal catalyst. This spent Au / Al₂O₃ catalyst contains 850 g / t Au₂O₃, 88.5 wt% Al₂O₃, and also contains 4.2 wt% carbon deposits (a byproduct of the reaction), 2.8 wt% KCl, and trace amounts of heavy metals such as Fe / V / Ni. Gold is primarily dispersed in nanoparticle form (5–50 nm) within the micropores of the Al₂O₃ support, but the pores are severely blocked by carbon and KCl deposits. Pretreatment is required before the experiment, including: calcination to remove carbon, calcining the spent catalyst in air at 450°C for 2 h to remove carbon deposits; and water washing for desalination, washing the calcined product with deionized water at 60°C with stirring for 2 h (liquid-to-solid ratio 5:1) to remove soluble KCl, and filtering and drying the washed product. This cyanide leaching gold process includes the following steps: Waste precious metal catalyst was ball-milled to a particle size of -0.074 mm (85%), and water was added to adjust the slurry concentration to 20%. Then, NaOH was added to adjust the pH of the slurry to 10, and NaCN was added for cyanidation treatment (NaCN dosage was 4.0 kg / t), controlling the free cyanide concentration of the slurry to 0.10%. Then, the controlled-release microsphere cyanidation aid prepared in Example 1 (dosage was 5.0 kg / t) was added, and the mixture was stirred and leached at 35°C for 72 h.

[0071] Comparative Example 7 This comparative example provides a cyanide leaching process for gold, which differs from Example 4 in that no leaching aid is added during the process; the dissolved oxygen in the slurry is used solely as the oxidant, the amount of NaCN used is 5.0 kg / t, and the leaching time is extended to 120 h. The remaining steps are the same as in Example 4 and will not be repeated here.

[0072] Comparative Example 8 This comparative example provides a cyanide leaching process for gold, which differs from Example 4 in that the controlled-release microsphere cyanide leaching aid prepared in Example 1 is not added, but ultrasonic assistance (power 200 W) is used during the cyanide leaching test. The remaining steps are the same as in Example 4 and will not be repeated here.

[0073] Example 5 This embodiment provides a cyanide leaching gold process, using the controlled-release microsphere cyanide leaching aid prepared in Example 1 to cyanide leach gold onto a gravity concentrate. The gravity concentrate has an Au grade of 850 g / t, Ag of 100 g / t, Fe of 28.6 wt% (mainly pyrite), As of 1.8 wt%, S of 18.2 wt%, Pb of 0.45 wt%, and Zn of 0.12 wt%. The gold is primarily coarse-grained native gold, partially coated with a Fe(OH)3 / FeOOH film formed by the oxidation of the pyrite surface. This cyanide leaching gold process includes the following steps: The ore was crushed to a fineness of -0.074 mm (90%), and water was added to adjust the slurry concentration to 33%. Then, an alkaline pH adjuster (NaOH) was added to adjust the pH of the slurry to 10.5. Next, NaCN was added for cyanidation treatment (NaCN dosage was 3.2 kg / t), and the free cyanide concentration of the slurry was controlled to be 0.07%. Then, the controlled-release microsphere cyanidation aid prepared in Example 1 (dosage was 2.5 kg / t) was added, and the mixture was stirred and leached at 25°C for 24 hours.

[0074] Comparative Example 9 This comparative example provides a cyanide leaching process for gold, which differs from Example 5 in that no leaching aid is added during the process; the dissolved oxygen in the slurry is used solely as the oxidant, and the amount of NaCN used is 4.0 kg / t. The remaining steps are the same as in Example 5 and will not be repeated here.

[0075] Comparative Example 10 This comparative example provides a cyanide leaching process for gold, which differs from Example 5 in that the controlled-release microsphere cyanide leaching aid prepared in Example 1 is not added; instead, Pb(NO3)2 is added at a dosage of 50 g / t. The remaining steps are the same as in Example 5 and will not be repeated here.

[0076] Comparative Example 11 This comparative example provides a cyanide leaching process for gold, which differs from Example 5 in that the controlled-release microsphere cyanide leaching aid prepared in Example 1 is not added; instead, SR-K2S2O8 drug-loaded micropowder prepared in Comparative Example 1 is added at a dosage of 2.0 kg / t. The remaining steps are the same as in Example 5 and will not be repeated here.

[0077] II. Analysis of Test Results for Each Embodiment and Comparative Example To analyze the sustained-release effect of the chitosan controlled-release shell, the cumulative release rate of K2S2O8 was tested on the controlled-release microsphere cyanide leaching aid prepared in Example 1 and the SR-K2S2O8 drug-loaded micropowder prepared in Comparative Example 1 under simulated cyanide leaching conditions (pH=10.5, temperature 25℃). The results are shown in Table 1.

[0078] Table 1. Cumulative release rate of K2S2O8 at different time points As shown in Table 1, the cumulative release rate of the controlled-release microsphere cyanide co-leaching agent prepared in Example 1 was 5.2% at 1 h, 10.8% at 2 h, 22.5% at 4 h, 41.7% at 8 h, 58.3% at 12 h, 82.1% at 24 h, 94.5% at 36 h, and 98.2% at 48 h. In contrast, the SR-K2S2O8 drug-loaded micropowder prepared in Comparative Example 1 achieved a cumulative release rate of 82.3% within 1 h, 95.6% after 2 h, and was almost completely released (99.1%) after 4 h, exhibiting typical rapid-release characteristics. In summary, this indicates that the chitosan controlled-release shell coating on the outside of the SR-K2S2O8 drug-loaded micropowder prepared in Example 1 can effectively slow down the release rate of potassium persulfate, achieving the target of controlled-release.

[0079] To analyze the effect of controlled-release microsphere cyanidation aid in the cyanidation leaching of arsenic-containing pyrite-type refractory gold ores, comparative experiments were conducted on Example 2 and Comparative Examples 2-4, and the results are shown in Table 2.

[0080] Table 2 Comparison of cyanide leaching test results for arsenic-bearing pyrite-type gold ores As shown in Table 2, in Comparative Example 2, without adding any leaching aid and relying solely on dissolved oxygen in the slurry, the gold leaching rate was only 78.5%, and the NaCN consumption was 2.0 kg / t. In Comparative Example 3, after adding the SR-K2S2O8 loaded micropowder prepared in Comparative Example 1, the gold leaching rate increased to 81.2%, but the NaCN consumption increased to 2.6 kg / t. In Comparative Example 4, after adding CaO2, the gold leaching rate was 80.8%, and the NaCN consumption was 2.3 kg / t. However, in Example 2, using the controlled-release microsphere cyanide leaching aid prepared in Example 1, the gold leaching rate still reached 86.7% even with the NaCN dosage reduced to 1.6 kg / t, and the NaCN consumption was only 1.7 kg / t. In summary, this indicates that the controlled-release microsphere cyanide leaching aid has a significant leaching effect in arsenic-bearing pyrite-type gold ores, effectively improving the gold leaching rate while significantly reducing sodium cyanide consumption.

[0081] To analyze the effect of controlled-release microsphere cyanide leaching aid in the re-leaching of residual gold in cyanide-containing tailings, comparative experiments were conducted on Example 3 and Comparative Examples 5-6, and the results are shown in Table 3.

[0082] Table 3 Comparison of Relative Gold Releaching Test Results in Cyanide-Containing Tailings As shown in Table 3, in Comparative Example 5, the gold leaching rate was only 32.1% with conventional cyanide leaching, NaCN consumption was 3.0 kg / t, and Fe dissolution was 12.5 mg / L. In Comparative Example 6, the gold leaching rate increased to 48.6% after oxalic acid reduction leaching, but NaCN consumption increased to 3.2 kg / t, and Fe dissolution increased sharply to 85.3 mg / L. In contrast, in Example 3, using the controlled-release microsphere cyanide leaching aid prepared in Example 1, the gold leaching rate significantly increased to 68.4%, NaCN consumption decreased to 2.6 kg / t, and Fe dissolution was only 28.7 mg / L. In summary, this indicates that the controlled-release microsphere cyanide leaching aid can effectively break the encapsulation of residual gold by iron oxides / hydroxides, and compared with the oxalic acid reduction leaching method, it has a higher gold leaching rate and a lower iron dissolution.

[0083] To analyze the effect of controlled-release microsphere cyanide leaching aid in gold recovery from waste precious metal catalysts, comparative experiments were conducted on Example 4 and Comparative Examples 7-8, and the results are shown in Table 4.

[0084] Table 4 Comparison of gold recovery test results from waste precious metal catalysts As shown in Table 4, in Comparative Example 7, with conventional cyanide leaching and an extended leaching time of 120 h, the gold leaching rate was 72.6%, and the NaCN consumption was 5.0 kg / t. In Comparative Example 8, after ultrasonic-assisted enhanced leaching, the gold leaching rate increased to 81.3%, but the NaCN consumption increased to 5.5 kg / t. In contrast, in Example 4, using the controlled-release microsphere cyanide leaching aid prepared in Example 1, the gold leaching rate reached as high as 96.2% under the conditions of NaCN dosage of 4.0 kg / t and a leaching time of only 72 h, with a NaCN consumption of only 3.8 kg / t. In summary, this indicates that the controlled-release microsphere cyanide leaching aid can effectively unclog the gold blocked by carbon deposits and sediments in the micropores of the spent catalyst, and compared with ultrasonic-assisted physical enhancement methods, it has a higher gold leaching rate and lower sodium cyanide consumption.

[0085] To analyze the effect of controlled-release microsphere cyanidation aid in the cyanidation leaching of gravity concentrate, comparative experiments were conducted on Example 5 and Comparative Examples 9-11, and the results are shown in Table 5.

[0086] Table 5 Comparison of cyanide leaching test results of gravity separation concentrate As shown in Table 5, in Comparative Example 9, the gold leaching rate was 82.6% during conventional cyanide leaching, the NaCN consumption was 4.0 kg / t, and the Fe²⁺ leaching rate was [missing value]. + The leaching concentration was 45.8 mg / L; in Comparative Example 10, the addition of Pb(NO3)2 increased the gold leaching rate to 86.4%, and the NaCN consumption increased to 4.2 kg / t, Fe² + The leaching concentration was 48.3 mg / L; in Comparative Example 11, after adding the SR-K2S2O8 drug-loaded micropowder prepared in Comparative Example 1, the gold leaching rate was 84.1%, and the NaCN consumption increased sharply to 5.8 kg / t, Fe² + The leaching concentration was 52.1 mg / L; however, in Example 5, after using the controlled-release microsphere cyanide leaching aid prepared in Example 1, the gold leaching rate was significantly increased to 95.3%, the NaCN consumption was reduced to 3.0 kg / t, and the Fe²⁺ concentration was reduced to 52.1 mg / L. + The leaching concentration was only 31.6 mg / L. In summary, this indicates that the controlled-release microsphere cyanide leaching aid can effectively inhibit the hindrance of gold leaching to the oxide film on the pyrite surface, significantly improving the gold leaching rate while substantially reducing sodium cyanide consumption and Fe²⁺. + Dissolution.

[0087] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing embodiments by combining some of the constituent elements, are also included in the scope of this application without departing from the spirit of this application.

[0088] Furthermore, although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing a controlled-release microsphere cyanide leaching aid, characterized in that, Includes the following steps: S1. Provide mesoporous silica powder; S2. The mesoporous silica powder is subjected to at least one potassium persulfate loading treatment to obtain SR-K2S2O8 drug-loaded micro powder; wherein, the potassium persulfate loading treatment includes: immersing the mesoporous silica powder in a saturated aqueous solution of potassium persulfate, removing it after thorough immersion and drying it. S3. The SR-K2S2O8 drug-loaded micro powder is subjected to at least one chitosan impregnation treatment, followed by cross-linking treatment, and filtered to obtain a wet filter cake after chitosan cross-linking. S4. The wet filter cake is granulated and dried to obtain a mesoporous silica-supported potassium persulfate-chitosan controlled-release microsphere cyanide impregnation aid.

2. The method for preparing the controlled-release microsphere cyanide leaching aid according to claim 1, characterized in that, In step S1, the mesoporous silica powder is synthesized using a template method; and / or, The mesoporous silica powder has a specific surface area of ​​500–1000 m² / g and a pore size of 2–10 nm.

3. The method for preparing the controlled-release microsphere cyanide leaching aid according to claim 1, characterized in that, In step S2, the pressure of the potassium persulfate loading treatment is -0.1 to -0.08 MPa, the liquid-solid ratio of the potassium persulfate saturated aqueous solution to the mesoporous silica powder is 5:1 to 10:1, and the time for full impregnation is 30 to 60 min; the drying is carried out under vacuum conditions at a temperature of 40 to 60°C for 12 to 24 h.

4. The method for preparing the controlled-release microsphere cyanide leaching aid according to claim 1, characterized in that, In step S2, the loading of potassium persulfate is 8% to 15% of the mass of mesoporous silica.

5. The method for preparing the controlled-release microsphere cyanide leaching aid according to claim 1, characterized in that, In step S3, the chitosan impregnation process includes: immersing the SR-K2S2O8 drug-loaded micropowder in a chitosan solution for 10-30 seconds, then removing it and air-drying it for 10-20 minutes. The method for preparing the chitosan solution includes: dissolving chitosan in a 0.5-1.5 vol% aqueous acetic acid solution; wherein the chitosan solution has a mass concentration of 1%-4%, a degree of deacetylation of ≥90%, and a molecular weight of 50,000-150,000 Da.

6. The method for preparing the controlled-release microsphere cyanide leaching aid according to claim 5, characterized in that, In step S3, the crosslinking treatment includes: adding the micro powder obtained after the chitosan impregnation treatment to a glutaraldehyde aqueous solution with a mass concentration of 5% to 10% to carry out a crosslinking reaction; The mass ratio of glutaraldehyde in the glutaraldehyde aqueous solution to chitosan is 1-3:10; the degree of crosslinking in the crosslinking reaction is 10%-30%, the reaction temperature is 25-35℃, and the reaction time is 1-3 h.

7. A controlled-release microsphere cyanide leaching aid, characterized in that, Prepared by the preparation method according to any one of claims 1-6; The impregnation aid includes core-shell structured microspheres, which comprise: a mesoporous silica carrier core and a chitosan controlled-release shell layer. The mesoporous silica carrier core is loaded with potassium persulfate within its mesoporous channels, and the chitosan controlled-release shell layer coats the surface of the mesoporous silica carrier core.

8. The controlled-release microsphere cyanide leaching aid according to claim 7, characterized in that, The average particle size of the mesoporous silica carrier core is 50–200 nm; the thickness of the chitosan controlled-release shell is 50–300 nm; and the total particle size of the controlled-release microsphere cyanide co-impregnation agent is 300–500 μm.

9. A cyanide immersion gold process, characterized in that, The cyanide leaching of gold using the controlled-release microsphere cyanide leaching aid as described in claim 7 or 8 comprises the following steps: Gold-containing materials are pretreated to obtain gold-containing powder; The gold-containing powder is subjected to slurry preparation to obtain the first slurry; An alkaline pH adjuster is added to the first slurry to obtain a second slurry; Sodium cyanide was added to the second slurry to obtain the third slurry; The controlled-release microsphere cyanide leaching aid is added to the third slurry, and the mixture is stirred and leached to obtain a gold-containing cyanide precious solution.

10. The cyanide immersion gold process according to claim 9, characterized in that, The pretreatment includes grinding or crushing; and / or, The gold powder concentration in the first slurry is 20%–45%; and / or, The pH value of the second slurry is 10–11.5; and / or, The free cyanide concentration of the third slurry is 0.02%–0.15%; and / or, The amount of the controlled-release microsphere cyanidation aid is 0.2–10.0 kg / t.